Trust and its meaning within the patient-doctor relationship in chosen codes of medical ethics - Adam Skowron (Kazimierz Wielki University, 2018)
In all the codes of ethics discussed here, the relationship of mutual trust is of great importance. If it arises, then it should certainly be actively cared for by the doctor. However, if it is absent, the doctor faces a dilemma: should contact with the patient be maintained at any cost? As I have shown, codes of ethics handle this situation, in which the relationship of mutual trust is somehow impaired, in various ways. The proposed answer to this question can therefore also vary. This is due to the fact that ethics is a set of rules operating "from within", which makes it different from the law. It would be absurd to claim that the standards of the Czech code of medical ethics apply solely to Czechs, while those of the Codex Deontologicus solely to Italians. One is a doctor not only always, but also everywhere. In the end, it is doctors who decide, according to their conscience, if their actions (in this case discontinuing treatment due to lack of mutual trust) are right or not. The criterion for rightness here is the best interest of the patient. However, the decision to discontinue treatment should be of a procedural nature. Only when a doctor has decided that all attempts to restore this relationship have failed, and when a more or less objective justification for cutting ties with the patient can be found, should the patient be handed over to another doctor.